Proceedings of the Ocean Drilling Program 1995
DOI: 10.2973/odp.proc.sr.144.068.1995
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Basalts from the West Pacific Guyots, Legs 143 and 144

Abstract: Volcanic rocks recovered during Legs 143 and 144 on the Allison, Resolution, Lo-En, Wodejebato, and MIT guyots belong to intraplate alkaline basalts. The basalts are strongly altered by hydrothermal processes, and some are affected by subaerial weathering. The low-temperature hydrothermal alteration, which is best represented in inner parts of sills on the Allison Guyot, led mainly to the formation of smectite, swelling chlorite, mixed-layer smectite-chlorite, and carbonates. Kaolinite, smectite, and hematite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Mixed-layer chlorite-swelling chlorite dominates in the flow interior. A similar distribution of secondary minerals and lack of vertical zonation were recognized in the West Pacific Guyots, Hole 865A, Legs 143 and 144 (Kurnosov et al, 1995). Basalt flows in Allison Guyot suffered lowtemperature smectitization, mainly in the upper parts of the units, and chloritization (swelling chlorite and mixed-layer smectite-chlorite mineral) in the interior.…”
Section: Hole 1138asupporting
confidence: 59%
See 1 more Smart Citation
“…Mixed-layer chlorite-swelling chlorite dominates in the flow interior. A similar distribution of secondary minerals and lack of vertical zonation were recognized in the West Pacific Guyots, Hole 865A, Legs 143 and 144 (Kurnosov et al, 1995). Basalt flows in Allison Guyot suffered lowtemperature smectitization, mainly in the upper parts of the units, and chloritization (swelling chlorite and mixed-layer smectite-chlorite mineral) in the interior.…”
Section: Hole 1138asupporting
confidence: 59%
“…DATA REPORT: ALTERATION OF BASALTS 2 teaus represent giant structures on the ocean floor that are often linear and extend several thousand kilometers to form large igneous provinces (LIPs). These structures reveal the characteristic features of magma composition, extrusion environment (from shallow-water and subaerial to deepwater environments), thermal history, and circulation of both seawater and meteoric fluids (Kurnosov et al, 1995;Kurnosov and Murdmaa, 1996). Variation in tectonic setting during the formation of these volcanic structures leads to significant variation in chemical composition of lava flows and pillow units (Vallier et al, 1981).…”
Section: Introductionmentioning
confidence: 99%
“…We also cannot exclude the possibility that the Ligurian filaments are alteration products of asbestiform serpentine or clay minerals. It has been observed that fibrous crystals are long and flexible, and can somewhat resemble endolithic microbial filaments (Muscente et al., 2018); they can also radiate from vesicle walls in altered marine basalt (Kurnosov et al., 1995). The filaments in our samples do not consist of single or bundled crystal fibers, as seen in asbestiform minerals, but might perhaps derive from the breakdown and recrystallization of fibers.…”
Section: Discussionmentioning
confidence: 99%